Educating Patients and the Community on Overcoming Anxiety During MRI (Magnetic Resonance Imaging) Examinations at the Radiology Department of RSI.Siti Rahmah - Santa Mareta; Oktavia Puspita Sari; Yori Rahmadianti (PT. Anagata Sembagi Education, 2025)
Magnetic Resonance Imaging (MRI) examinations often cause significant anxiety in patients due to unfamiliar surroundings, loud noises, confined spaces, and a lack of understanding about the procedure. This anxiety can trigger uncontrolled movement during the scan, which affects image quality and causes artifacts. This Community Service Activity (PKM) aims to educate patients, the community, and radiographers on techniques for managing anxiety before and during MRI examinations. Participatory methods through counseling, interactive discussions, and relaxation technique simulations were implemented at the Radiology Installation of RSI Siti Rahmah Padang. Evaluation using pre-tests and post-tests on 15 radiographers showed an increase in average understanding from 45% to 85% (a 40% increase). A satisfaction survey of 25 participants (radiographers, patients, and companions) showed that an average of 94.5% of respondents were satisfied with the material, methods, and benefits of the activity. These results confirm the effectiveness of interactive education in improving the competence of radiographers and the psychological readiness of patients, which ultimately contributes to improving the quality of radiology services based on patient-centered care